PERKAWINAN SEBAGAI IBADAH: REORIENTASI NIAT DALAM PEMBENTUKAN KELUARGA ISLAMI - Muhammad Ahmad Fulka Sa'dibih (Tamaddun, 2025)
This article explores the importance of reorienting intentions in marriage to reaffirm the understanding of marriage as an act of worship in Islamic perspective. Using a theological-descriptive approach, the study examines the concept of niyyah in the Qur’an, hadith, and the views of classical and contemporary scholars. The findings indicate that the proper orientation of intention serves as a spiritual and moral foundation in building a sakinah, mawaddah, wa rahmah family. Reorienting intentions from worldly purposes toward worship consciousness plays a crucial role in shaping ethical relationships, responsibility, and blessings in Islamic marital life.